2010
DOI: 10.1673/031.010.3501
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology Caused by the Entomopathogenic Fungi,Beauveria bassianaandMetarhizium anisopliae, in the Adult Planthopper,Peregrinus maidis, a Maize Virus Vector

Abstract: The planthopper Peregrinus maidis (Ashmead) (Hemiptera: Delphacidae) is an important vector of maize viruses in tropical and subtropical areas. Planthoppers are biologically controlled with several species of entomopathogenic fungi that have been isolated from these insect pests of rice in Asia. Beauveria bassiana (Balsamo-Crivelli) Vuillemin and Metarhizium anisopliae (Metschnikoff) Sorokin (Hypocreales: Clavicipitaceae) appear to be the most useful against planthoppers because of their ease of mass productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 20 publications
5
25
0
4
Order By: Relevance
“…On the sixth dpi the larvae began to die and on the seventh dpi all the larvae were dead. These dark spots corroborated previous studies (ALVES, 1998;TOLEDO et al, 2010) and confirmed what is known about the integument of insects being the main route of entomopathogenic fungal entry, including M. anisopliae; the dark spots were the result of fungal germination and penetration in the cuticle through the action of extracellular enzymes and mechanical pressure exerted by hyphae.…”
Section: Metarhiziumsupporting
confidence: 91%
See 2 more Smart Citations
“…On the sixth dpi the larvae began to die and on the seventh dpi all the larvae were dead. These dark spots corroborated previous studies (ALVES, 1998;TOLEDO et al, 2010) and confirmed what is known about the integument of insects being the main route of entomopathogenic fungal entry, including M. anisopliae; the dark spots were the result of fungal germination and penetration in the cuticle through the action of extracellular enzymes and mechanical pressure exerted by hyphae.…”
Section: Metarhiziumsupporting
confidence: 91%
“…This was related to the availability of nutrients in tissues because, as pointed out by TOLEDO et al(2010), nutrient limitation leads to the formation of hyphae with a smaller diameter. Fatty tissue is another preferential target.…”
Section: Metarhiziummentioning
confidence: 98%
See 1 more Smart Citation
“…In the colonization events observed by Toledo et al (2010) in the planthopper Peregrinus maidis (Hemiptera: Delphacidae) traited by B. bassiana and Metarhizium anisopliae, the formation and multiplication of hyphal bodies by both fungal species inside the host's body was noted. The host's whole body was invaded by hyphae between five and six days post-inoculation, and body fat was the most affected tissue.…”
Section: Results Of Histological Studymentioning
confidence: 99%
“…Serangga uji yang diaplikasikan bioinsektisida menghasilkan LT 50 sebesar 3-4 hari. Toledo et al (2010) mendapat kecenderungan yang sama karena cendawan butuh waktu untuk berkecambah, mulai dari perkecambahan konidia membutuhkan 24-48 jam, setelah 72 jam tabung kecambah sudah dapat ditemukan pada kutikula integumen serangga inang tersebut.…”
Section: A B a Bunclassified